Hydration dependent dynamics in RNA - Olsen, Greg L.; Bardaro Jr., Michael F.; Echodu, Dorothy C.; Drobny, Gary P.; Varani, Gabriele (Journal of biomolecular NMR, 2009)
The essential role played by local and collective motions in RNA function has led to a growing interest in the characterization of RNA dynamics. Recent investigations have revealed that even relatively simple RNAs experience complex motions over multiple time scales covering the entire ms–ps motional range. In this work, we use deuterium solid-state NMR to systematically investigate motions in HIV-1 TAR RNA as a function of hydration. We probe dynamics at three uridine residues in different structural environments ranging from helical to completely unrestrained. We observe distinct and substantial changes in 2H solid-state relaxation times and lineshapes at each site as hydration levels increase. By comparing solid-state and solution state 13C relaxation measurements, we establish that ns–ls motions that may be indicative of collective dynamics suddenly arise in the RNA as hydration reaches a critical point coincident with the onset of bulk hydration. Beyond that point, we observe smaller changes in relaxation rates and lineshapes in these highly hydrated solid samples, compared to the dramatic activation of motion occurring at moderate hydration.
Keywords: RNA; Dynamics; Hydration; Solid state NMR; Deuterium NMR; Relaxation